Electromyographic assessment of trunk and shoulder muscles during a Pilates pull-up exercise - Isabel C.N. Sacco; Eduardo T.T. Mori; Bergson C. Queiroz; Nadia Marconi; Ivye L. R. Pereira (Universidade Estadual Paulista (UNESP), 2014)
This study compares surface electromyographic activity of the internal oblique, rectus abdominis, multifidus, iliocostalis, anterior deltoids during the pull-up on a lower and on a higher difficulty level. We assessed nine adults with previous experience in Pilates. The root mean square (RMS) values were normalized by maximum isometric contraction for each participant. During the ascent phase, the low spring position showed a significantly higher RMS than the high spring position of 8.9% for deltoid, 17.2% for internal oblique, 22.3% for rectus abdominis, 4.1% for iliocostalis, and 5.6% for multifidus, and in the descent phase, the RMS in the lower spring exceeded significantly the high spring position in 1.6% for the deltoid, 10% for internal oblique, 31.4% for rectus abdominis and 11.4% for iliocostalis. There was no predominance of abdominal muscles over the shoulder muscle in any spring position. The pull-up exercise can be a useful choice for the core and anterior deltoid muscles strengthening.